THE MIDDLE BRONZE AGE IN BANAT. OLD CONTROVERSIES ON THE VATINA CULTURE - GOGÂLTAN, Florin (Studia Universitatis Babeș-Bolyai Historia, 2023)
Nearly 20 years ago I presented a brief historiographical overview of the so-called Vatina culture. Being published in Romanian, the article had a limited distribution. My concluding remarks on the so-called Corneşti-Crvenka group were the only ones noticed, probably because they were included in the English summary. Now I found it useful to publish in English this historiographical work concerning the Vatina culture, because it is still relevant today and can be the basis for future discussions concerning the Middle Bronze Age in the historical Banat. Cu aproape 20 de ani în urmă prezentam o schiță istoriografică privind aşa numita cultură Vatina. Fiind publicat în limba română, articolul a avut o circulație restrânsă. Au fost remarcate doar concluziile mele referitoare la aşa-numitul grup Corneşti-Crvenka, care se regăseau în rezumatul în limba engleză. Am considersat utilă publicarea în limba engleză a acestui demers istoriografic privind cultura Vatina, care este încă actual, pe care se pot clădi viitoare discuții privind bronzul mijlociu în Banatul istoric. Cuvinte-cheie: Banat, bronz mijlociu, cultura Vatina, perspectivă istoriografică Article: archeology; Received: 15.03.2023; Revised: 17.03.2023 Accepted: 18.03.2023; Available online: 28.04.2023.